Compressing Images Using Multi-Level Wavelet Transform Algorithm (MWTA) - Odeh, Ali Ahmad Alabd Abu (2012)
This study aims to use Wavelet Transform Algorithm for image compression. Multi-levels were used in this study with the aim to produce better results for compressing images.The Multi-level Wavelet Transform Algorithm (MWTA) consists of three phases namely, first level compression, second level compressing in the first level, and algorithm validation by compare.Therefore, Vaishnavi method is used to design and develop the prototype model.In this study, the experiment was conducted using different images (RGB). The algorithm and comparison was simulated using Matlab application. The results revealed that Multi-level Wavelet Transform Algorithm (MWTA) can be used in more than one level in this algorithm but the efficiency of this algorithm for compressing was found to be in the first level in terms of size.